Internal Gravity Waves in the Shallow Seas - R. Massel, Stanisław (GeoPlanet: Earth and Planetary Sciences,, 2015)
This book contains a comprehensive study of the internal ocean waves, which play a very important role in ocean physics providing mechanisms for ocean water mixing and circulation, as well as the transportation of gases, nutrients, and a very large number of marine organisms in the ocean body. In contrast to surface waves, the literature on internal waves is not so numerous, mainly due to the difficulties in experimental data collection and in the mathematical description of internal wave propagation. In this book, the basic mathematical principles, a physical description of the observed phenomena, and practical theoretical methods of determination of wave parameters as well as the original method of observation using moving sensors are presented. Special attention is paid to internal wave propagation  over changing bottom topographies in shallow seas such as the Baltic Sea. The book is supplemented with an extended list of relevant and extended bibliographies, a subject index, and an author index.